Monitoring and Control System of Parallel Loads Electricity Consumption Based on IOT - M. Teguh Adkhar; Hasti Afianti (JEECS (Journal of Electrical Engineering and Computer Sciences), 2023)
This paper discusses the design of a power consumption monitoring using telegrams and LCDs. Monitoring of electrical energy consumption is carried out for overconsumption does not occur as well as safeguarding the electronic devices used. The relay will automatically disconnect the power source in every room when the power is overloaded and this condition is reported via the internet network with the Telegram application. To monitor power usage, it is necessary to measure it. Measurement in this study used a digital multi-meter and the PZEM-004T sensor. Measurements were made on ten electrical loads including Lights, fans, laptop chargers, cell phone chargers, soldering iron, grinders, iron hand drills, drill bits, and circular grinding wheels. The test to compare PZEM-004T and multimeter has been done, resulting in voltage error values of 0.048-1.347% and current error values of 0-35.484%. From the error value obtained in this test, it can be concluded that the PZEM004T is suitable for measuring current and voltage. Automatic control in the relay works when rooms 1, 2, 3, or 4 experience power readings that exceed the desired capacity. It will automatically cut off the voltage from the source so that excess power does not occur, the goal is to protect an electric circuit.